Ultrafast Long-Distance Electron-Hole Plasma Expansion in GaAs Mediated by Stimulated Emission and Reabsorption of Photons - Troha, Tinkara; Klimovič, Filip; Ostatnický, Tomáš; Kadlec, Filip; Kužel, Petr; Němec, Hynek (Physical review letters, 2023)
Electron-hole plasma expansion with velocities exceeding c/50 and lasting over 10 ps at 300 K was evidenced by time-resolved terahertz spectroscopy. This regime, in which the carriers are driven over >30 μm is governed by stimulated emission due to low-energy electron-hole pair recombination and reabsorption of the emitted photons outside the plasma volume. At low temperatures a speed of c/10 was observed in the regime where the excitation pulse spectrally overlaps with emitted photons, leading to strong coherent light-matter interaction and optical soliton propagation effects.
Keywords: Gallium; galium; arsenikové přípravky; Arsenicals; Photons; fotony; elektrony; Electrons